Postoperative urinary tract infection after ureteroscopic lithotripsy in patients with asymptomatic bacteriuria - Jovanović, Mirko; Šuljagić, Vesna; Bančević, Vladimir (Vojnosanitetski pregled, 2021)
Background/Aim. Postoperative urinary tract infection (UTI) is one of the most common infective complications of ureteroscopic lithotripsy. Preoperative asymptomatic bacteriuria is not a contraindication for performing ureteroscopic lithotripsy but it can be a significant risk factor for occurrence of severe forms of postoperative urinary infection. Methods. From January 2010 until December 2014 at the Urology Clinic of the Military Medical Academy in Belgrade, 389 patients undergoing ureteroscopic lithotripsy were analyzed, and their postoperative infective complications were monitored. From the group, the incidence of posteoperative urinary infection was analysed in 52 patients with preoperative asymptomatic bacteriuria. Results. Infective complications occured in 18.7% of patients, and postoperative UTI in 10% of patients. Out of 52 patients with preoperative asymptomatic bacteriuria, 36.5% had postoperative urinary tract infection (χ2 = 46.773; p < 0.001). In these patients, we registered higher frequency of severe forms of postoperative UTI, systemic inflammatory response syndrome (SIRS) and sepsis. Conclusion. Preoperative asymptomatic bacteriuria represents a significant risk factor for developing postoperative UTI following ureteroscopic lithotripsy and is associated with increased risk for occurence of severe forms of SIRS and sepsis. It is desirable that every patient with indicated ureteroscopic lithotripsy has sterile urine culture, and if this is impossible to achieve, a special caution and an adequate antibiotic therapy and prophylaxis are needed before and during the surgical procedure.